1999
DOI: 10.1099/00221287-145-11-3129
|View full text |Cite
|
Sign up to set email alerts
|

Sequence analysis of three Bacillus cereus loci carrying PlcR-regulated genes encoding degradative enzymes and enterotoxin The EMBL accession numbers for the sequences reported in this paper are given in Table 1 T1 .

Abstract: PlcR is a pleiotropic regulator of extracellular virulence factors in the opportunistic human pathogen Bacillus cereus and the entomopathogenic Bacillus thuringiensis, and is induced in cells entering stationary phase. Among the genes regulated by PlcR are : plcA, encoding phosphatidylinositol-specific phospholipase C (PI-PLC) ; plc, encoding phosphatidylcholine-preferring phospholipase C (PC-PLC) ; nhe, encoding the non-haemolytic enterotoxin ; hbl, encoding haemolytic enterotoxin BL (HBL) ; and genes specify… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
65
0

Year Published

2002
2002
2007
2007

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 106 publications
(67 citation statements)
references
References 51 publications
(43 reference statements)
2
65
0
Order By: Relevance
“…The B. cereus group isolates were widely distributed in a phylogenetic tree constructed by multilocus enzyme electrophoresis analysis (13; E. Helgason, personal communication) and were all found to harbor the bcr1 repeat, while no repeats were identified in the 11 Bacillus strains outside the group (Table 1). This finding suggests that bcr1 may be ubiquitous and specific to members of the B. cereus group of bacteria and could be Table 1 (25,26), bcr1 could be found as a full-length repeat of ϳ155 bp or as shorter versions containing parts of the fulllength sequence. Here, our sequence searches detected 272 partial bcr1 elements (of a minimal defined length of 30 bp) in the three chromosomes altogether, and the ratio of full-length to partial copies was highly divergent among the strains (0. bcr1 chromosomal orientation and localization.…”
Section: Resultsmentioning
confidence: 87%
See 2 more Smart Citations
“…The B. cereus group isolates were widely distributed in a phylogenetic tree constructed by multilocus enzyme electrophoresis analysis (13; E. Helgason, personal communication) and were all found to harbor the bcr1 repeat, while no repeats were identified in the 11 Bacillus strains outside the group (Table 1). This finding suggests that bcr1 may be ubiquitous and specific to members of the B. cereus group of bacteria and could be Table 1 (25,26), bcr1 could be found as a full-length repeat of ϳ155 bp or as shorter versions containing parts of the fulllength sequence. Here, our sequence searches detected 272 partial bcr1 elements (of a minimal defined length of 30 bp) in the three chromosomes altogether, and the ratio of full-length to partial copies was highly divergent among the strains (0. bcr1 chromosomal orientation and localization.…”
Section: Resultsmentioning
confidence: 87%
“…Default values were employed for all other BLASTN parameters. A 141-bp sequence from the bcr1 element bcr1_trp1 (26) was originally used as the seed for the process. However, a comparison of the flanking regions of the sequences obtained after the first BLASTN run revealed that the bcr1 repeat could be redefined as a ϳ160-bp sequence flanked by TTTAT motifs.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The mini-Tn10 transposon conferred resistance to spectinomycin in E. coli (60 g/ml), making it possible to select clones transformed with fragments containing the insertion locus. The chromosomal DNA flanking the insertion locus was sequenced, primarily with primers binding to the extremities of the transposon, and the sequence obtained was extended by chromosome walking, using the chromosome of strain B. thuringiensis 407(Cry Ϫ ), as described in the work of Okstad et al (21). Part of this extended sequence was determined by M. Rose (Institut für Mikrobiologie, J. W. Göethe Universität, Frankfurt, Germany).…”
Section: Methodsmentioning
confidence: 99%
“…Bacteria of the Bacillus cereus phylogenetic group (B. cereus and Bacillus thuringiensis), to which B. anthracis belongs, secrete a diversity of factors that are essential for virulence, including toxins, hemolysins, proteases, and lecithinases. Notably, in these bacteria the secretion of certain virulence factors is regulated by a pleiotropic regulator, PlcR (2,82,87,110), which is inactive in B. anthracis (2). It has been suggested that the evolutionary inactivation of the PlcR regulon in B. anthracis was due to incompatibility with the AtxAcontrolled regulon and reflects the fact that the PlcR target genes are not essential for anthrax pathogenicity (96).…”
mentioning
confidence: 99%